The Performance and Role of Cottage Small-Scale Industries in India - PANDEY, DR. TARKESHWAR (IJRDO - Journal of Business Management, 2016)
The small scale industrial sector plays a vital role in the growth of the country. It contributes almost 40% of gross industrial value added in the Indian economy. It has been estimated that millions of investment in fixed assets in the small scale sector produces 4.62 million worth of goods or service with the approximate value addition of ten percent points. The small scale sector has grown rapidly over the year .The number of small scale units has from estimated 0.87 million units in the year 1980-81 to over 3 million in the year